Ephemeral wetland communities of Isoëto-Nano-Juncetea class – new data from south-eastern Poland - Krawczyk, Rafał; Cwener, Anna; Michalczuk, Wiaczesław; Zubel, Robert (Biodiversity: Research and Conservation, 2016)
Vegetation data (70 relevés) of ephemeral wetlands collected in both permanent and temporal water basins were analyzed. Numerical classification of the data revealed two distinct subsets, the first comprised communities of Eleocharition ovatae Philippi 1968 alliance, the second combined communities dominated by Alisma lanceolatum, Isolepis supina or Elatine alsinastrum (Alisma lanceolatum group). Phytocoenoses of Eleocharition ovatae were widely distributed in the study area and developed, most frequently, on exposed bottoms of fishponds. This group could be divided into four types of communities. Patches representing Alisma lanceolatum group were found only in mid-field depressions periodically filled with water and concentrated in Volhynian Upland. In this group, two lower vegetation units were distinguished.